Feeding preference of Euborellia annulipes to Plutella xylostella: effects of temperature and prey development stage - Nunes, Gilmar da Silva [UNESP]; Paulo, Hagabo Honorato de [UNESP]; Rocha Dias, Welliny Soares [UNESP]; De Bortoli, Sergio Antonio [UNESP] (Univ Federal Goias, 2020)
The ring-legged earwig Euborellia annulipes has been studied as a natural enemy of pest-insects and a potential predator of diamondback moth. Temperature is an important factor that mediates the pest population density and may affect the predator-prey relationship dynamics. This study aimed to evaluate the effect of the temperature and development stage of Plutella xylostella individuals on the feeding preference of E. annulipes females. Three temperatures (18 degrees C, 25 degrees C and 32 degrees C), two development stages (larvae and pupae) and two feeding conditions related to the prey capture (with or without choice) were assessed. No matter the temperature, ring-legged earwig females showed a preference for eating larvae, instead of pupae. The temperature and choice conditions influenced the amount of consumed preys, but only for larvae (not for pupae). The lowest larvae consumption was observed at 18 degrees C, in both prey capture conditions.
Keywords: Biological control; brassicas; earwig; integrated pest management; thermal conditions